IMPROVING DISTRIBUTION INVENTORY CONTROL THROUGH FIFO AND COSO FRAMEWORK AT PT. MITRA KENCANA DISTRIBUSINDO - Regina Luntungan; Sintia Nurani Korompis; Elisabeth Deisi Malonda; Noah Smith (Journal Markcount Finance, 2026)
This study aims to analyze the effectiveness of inventory internal control using the First In, First Out (FIFO) method at PT Mitra Kencana Distribusindo, particularly in the Non-Food Warehouse. This research employed a descriptive qualitative approach with an evaluative orientation based on the COSO internal control framework. Data were collected through structured interviews with two purposively selected informants, direct non-participant observation of warehouse activities, and documentation review of receiving notes, cash invoices, warehouse cards, stock opname documents, aging reports, non-food inventory data, and checker duty documents. Data analysis was carried out through data reduction, data display, and conclusion drawing by grouping the findings into the five COSO components and FIFO implementation criteria. The findings indicate that inventory control has been implemented through receiving and issuing procedures, segregation of duties, authorization, internal and external checker functions, warehouse cards, stock opname, aging reports, and FIFO-based inventory circulation. However, the control system is not yet fully optimal because several critical weaknesses remain, particularly incomplete batch/expiry information, limited written follow-up documentation for stock opname results, insufficient FIFO-based warehouse layout control, and inadequate follow-up records for discrepancies, returns, damaged goods, defective goods, and items approaching expiry. This study concludes that FIFO-based inventory internal control is sufficiently effective, but still requires stronger documentation, monitoring, and corrective action procedures to improve inventory accuracy, traceability, and risk responsiveness.